Results on total and elastic cross sections in proton-proton collisions at √s=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physics letters, 2020)
We report results on the total and elastic cross sections in proton-proton collisions at s=200 GeV obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section was measured in the squared four-momentum transfer range 0.045≤−t≤0.135 GeV2. The value of the exponential slope parameter B of the elastic differential cross section dσ/dt∼e−Bt in the measured −t range was found to be B=14.32±0.09(stat.)−0.28+0.13(syst.) GeV−2. The total cross section σtot, obtained from extrapolation of the dσ/dt to the optical point at −t=0, is σtot=54.67±0.21(stat.)−1.38+1.28(syst.) mb. We also present the values of the elastic cross section σel=10.85±0.03(stat.)−0.41+0.49(syst.) mb, the elastic cross section integrated within the STAR t-range σeldet=4.05±0.01(stat.)−0.17+0.18(syst.) mb, and the inelastic cross section σinel=43.82±0.21(stat.)−1.44+1.37(syst.) mb. The results are compared with the world data.
Im Titel steht "s" unter dem Wurzelsymbol
Gesehen am 27.10.2020